2003
DOI: 10.1055/s-2003-36966
|View full text |Cite
|
Sign up to set email alerts
|

Umfassende Lehrevaluation in der Medizin - eine Aufgabe für die psychosozialen Fächer?

Abstract: The paper describes the experiences with a comprehensive evaluation of medical teaching at the medical faculty of the Friedrich-Schiller-University Jena. Based upon evaluations of courses initiated by the students, the evaluation of teaching is organized scientifically and extended as a comprehensive evaluation of several relevant issues (e. g. surveys of teachers and alumni) by the staff of the Department of Medical Psychology since 1998. Originally supported by a grant of the state of Thuringia, the evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Two studies from Germany covering all years of undergraduate medical education obtained student ratings of their initial interest in course content. In one study, these were significantly and strongly correlated to post-course ratings of didactic quality [ 15 ], and the other study found a strong correlation with overall ratings obtained after course attendance [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies from Germany covering all years of undergraduate medical education obtained student ratings of their initial interest in course content. In one study, these were significantly and strongly correlated to post-course ratings of didactic quality [ 15 ], and the other study found a strong correlation with overall ratings obtained after course attendance [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a group of 40 second-year students at the University of California Medical Centre, those randomised to attend a live lecture provided more favourable ratings than those watching a video recording of the same lecture [ 21 ]. One German study found that mandatory seminars received more positive overall ratings than lectures with voluntary attendance [ 15 ]. At the same time, students voluntarily attending lectures tended to provide more positive ratings than non-attendees in this [ 15 ] and another [ 17 ] study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these evaluations provide a rough idea of student satisfaction with teaching, they are not considered valid measures of teaching quality due to the strong bias introduced by various construct-irrelevant confounders [5]. Data show for example that students with a high initial interest in a course generally tend to rate it more positively than those with a low interest [7], [8]. Further studies found a positive correlation between exam performance and student ratings for an anatomy course [9], [10].…”
Section: Discussionmentioning
confidence: 99%